MANJISTHA (RUBIA CORDIFOLIA) AS COSMECEUTICAL REMEDY FOR PREVENTION OF STRIAE GRAVIDARUM - Verma, *Sarita; Singh, D. C.; Singh, Ritu; Kumar Sanger, Rupesh (International Journal of Ayurveda and Pharma Research, 2017)
Cosmetics have important place in every women's life since ancient times. Women are more concern about their look during pregnancy as 90% cases develop striae marks on abdomen, breast and thighs or scratch marks due to itching make their look ugly. But there is a difference between cosmetic and cosmeceutical products which restrict sell of cosmetic without medical prescription if it contains ingredients that can penetrate or change the functioning of the skin. Cosmeceuticals are serving as a bridge between personal care products and pharmaceuticals. Manjistha can play a very good role in this burning issue of itching and striae marks due to their medicinal properties. Manjistha as remedy can prevent burning, itching and other fungal or bacterial infection and promotes skin healing by local action on skin and promotes collagen formation due to property of Ropana- Sothahar. Kandughana and Vishghana properties shows antiallergic action, anti bacterial, antifungal action actions prevents skin from secondary infection of skin caused due to itching. Pittashamak property pacify alleviated dosha and Varnya property promotes skin texture, colour and luster. Manjistha can acts as skin protective drug which is used in Striae gravidarum to relief basic symptom of hypopigmentation, itching burning and maintains skin luster so that drug can be used in cosmeceutical industry for prevention of striae gravidarum.